Tri-Ponderal Mass Index Vs. Fat Mass/Height(3) as a Screening Tool for Metabolic Syndrome Prediction in Colombian Children and Young People - Garcia-Hermoso, A (Multidisciplinary Digital Publishing Institute (MDPI), 2018)
Tri-ponderal mass index (TMI) and fat mass index (FMI) have been proposed as alternative approaches for assessing body fat since BMI does not ensure an accurate screening for obesity and overweight status in children and adolescents. This study proposes thresholds of the TMI and FMI for the prediction of metabolic syndrome (MetS) in children and young people. For this purpose, a cross-sectional study was conducted on 4673 participants (57.1% females), who were 9-25 years of age. As part of the study, measurements of the subjects weight, waist circumference, serum lipid indices, blood pressure and fasting plasma glucose were taken. Body composition was measured by bioelectrical impedance analysis (BIA). The TMI and FMI were calculated as weight (kg)/height (m(3)) and fat mass (kg)/height (m(3)), respectively. Following the International Diabetes Federation (IDF) definition, MetS is defined as including three or more metabolic abnormalities. Cohort-specific thresholds were established to identify Colombian children and young people at high risk of MetS. The thresholds were applied to the following groups: (i) a cohort of children where the girls TMI >= 12.13 kg/m(3) and the boys TMI >= 12.10 kg/m(3); (ii) a cohort of adolescents where the girls TMI >= 12.48 kg/m(3) and the boys TMI >= 11.19 kg/m(3); (iii) a cohort of young adults where the women s TMI >= 13.21 kg/m(3) and the men s TMI >= 12.19 kg/m(3). The FMI reference cut-off values used for the different groups were as follows: (i) a cohort of children where the girls FMI >= 2.59 fat mass/m(3) and the boys FMI 1.98 fat mass/m(3); (ii) a cohort of adolescents where the girls FMI >= 3.12 fat mass/m(3) and the boys FMI >= 1.46 fat mass /m(3); (iii) a cohort of adults where the women s FMI >= 3.27 kg/m(3) and the men s FMI >= 1.65 kg/m(3). Our results showed that the FMI and TMI had a moderate discriminatory power to detect MetS in Colombian children, adolescents, and young adults.